(untitled) (Superficies y Vacío, 2022)
In order to control the deposition of Zn-related films by chemical bath deposition, the effects of Zn-complexing agent are analyzed. ZnS films were produced by chemical bath deposition technique employing sodium citrate, ethanolamine and Triethanolamine as complexing agents. The deposition conditions for ZnS (ZnO) thin films were obtained through a thermodynamic analysis, using distribution diagrams for molar fraction of Zn complexes. From species distribution diagrams of Zn-ethanolamine, Zn-Triethanolamine and Zn-citrate. It was found that for pH values between 4 and 6 the highest Zn fraction is obtained. The results highlight the importance of complexing agent morphology, while the use of ethanolamine and triethanolamine produce ZnO films due to their high reactivity; the use of sodium citrate produce ZnS films. Deposited ZnS films have a cubic structure, n-type conductivity, resistivity of 8.36×104 ??cm with a 3.75 eV bandgap.